First-line erlotinib versus gemcitabine/cisplatin in patients with advanced EGFR mutation-positive non-small-cell lung cancer: analyses from the phase III, randomized, open-label, ENSURE study - Wu, Y-L; Zhou, C..; Liam, Chong-Kin; Wu, G.; Liu, X.; Zhong, Z.; Lu, S.; Cheng, Y.; How, Soon Hin; ., et al. (Oxford University Press on behalf of the European Society for Medical Oncology, 2015)
Background The phase III, randomized, open-label ENSURE study (NCT01342965) evaluated first-line erlotinib versus gemcitabine/cisplatin (GP) in patients from China, Malaysia and the Philippines with epidermal growth factor receptor (EGFR) mutation-positive non-small-cell lung cancer (NSCLC).